2014
DOI: 10.1088/1475-7516/2014/02/019
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar timing signal from ultralight scalar dark matter

Abstract: An ultralight free scalar field with mass around 10 −23 − 10 −22 eV is a viable dark mater candidate, which can help to resolve some of the issues of the cold dark matter on sub-galactic scales. We consider the gravitational field of the galactic halo composed out of such dark matter. The scalar field has oscillating in time pressure, which induces oscillations of gravitational potential with amplitude of the order of 10 −15 and frequency in the nanohertz range. This frequency is in the range of pulsar timing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
325
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(333 citation statements)
references
References 24 publications
7
325
1
Order By: Relevance
“…This appears to exclude the possibility to search for ULAs via pulsar timing experiments as proposed by Khmelnitsky & Rubakov (2014). We have found that ma = 10 −23 eV cannot produce enough galaxies of the required magnitude at high-z to be consistent with HUDF.…”
Section: Summary and Discussionmentioning
confidence: 68%
“…This appears to exclude the possibility to search for ULAs via pulsar timing experiments as proposed by Khmelnitsky & Rubakov (2014). We have found that ma = 10 −23 eV cannot produce enough galaxies of the required magnitude at high-z to be consistent with HUDF.…”
Section: Summary and Discussionmentioning
confidence: 68%
“…We focused in particular on gravitational effects, without making assumptions about the coupling of the scalar to other matter fields (except that the couplings are small enough so that the scalar DM survives until today). Other possible gravitational consequences of light scalars we did not discuss include superradiance of black holes [6,65], and effects on pulsar timing observations [66] or binary pulsars [67]. We also remark that concrete models of scalar DM can contain couplings with other fields, such as axion-type couplings to photons.…”
Section: Discussionmentioning
confidence: 96%
“…We highlight the relatively high signal strength we calculate for pulsars within the Galactic soliton region as a function of Axion mass in a series of curves, demonstrating that this signal is already detectable for central Galactic pulsars. For comparison, the diagonal dotted line is the prediction obtained by [7] for local pulsars, assuming a smooth density distribution, with the blue shaded region representing the wider range we predict that includes our de-Broglie scale DM density modulation. The local upper limit obtained by [35] is also shown (black square with arrow).…”
Section: Pairwise Timing Amplitudesmentioning
confidence: 92%
“…These oscillations are usually neglected as the average pressure over the period is zero. However, at the Compton scale of interest here, the oscillating scalar field generates an oscillating gravitational potential in proportion to the local mass density [7]. All clocks are modulated by such an oscillating field, including Earth clocks and Pulsars.…”
Section: Compton Scale Pressure Oscillation and Pulsar Timingmentioning
confidence: 99%